Upaya Peningkatan Hasil Belajar Melalui Model Pembelajaran Jigsaw - Masrifawati, Masrifawati (JURNAL GLOBAL EDUKASI, 2018)
Abstract: The implementation of classroom action research departs from the background of the need for renewal in teaching and learning activities both conducted by teachers and by students in particular. Thus class action research is very important role in improving the quality of learning activities so that teachers always hold innovations or updates both on planning, implementing, evaluating, and analyzing learning activities. This study aims to determine the Efforts to Increase Learning Outcomes Through Jigsaw Learning Methods With Material PKn Learning Experiences in Class I Students SD Negeri 014673 Mekar Sari district Buntu Paane academic year 2017/2018. Classroom action research was conducted in class I, which amounted to 20 students. The subjects of this study were class I PKN teachers and first grade students of SD Negeri 014673 Mekar Sari, data were collected through observation, interviews, tests, and documentation studies. This classroom action research is carried out in 2 cycles, each cycle consisting of planning, implementing actions, observing and reflecting. The results of the comparison of teacher research observations in the first cycle were 21% while in the second cycle it was 29%. Keyword: Jigsaw Learning Method Abstrak: Dilaksanakannya penelitian tindakan kelas ini berangkat dari latar belakang perlunya pembaruan dalam kegiatan belajar mengajar baik yang dilakukan oleh guru maupun oleh siswa khususnya. Dengan demikian penelitian tindakan kelas sangat berperanan penting dalam meningkatkan mutu kegiatan pembelajaran agar guru selalu mengadakan inovasi atau pembaharuan baik terhadap perencanaan, pelaksanaan, evaluasi, maupun menganalisis kegiatan pembelajaran. Penelitian ini bertujuan untuk mengetahui Upaya Peningkatan Hasil Belajar Melalui Metode Pembelajaran Jigsaw Dengan Materi Pengalaman Pelajaran PKn Siswa Kelas I SD NEGERI 014673 Mekar Sari kec. Buntu Pane TP. 2017/2018. Penelitian tindakan kelas dilaksanakan dikelas I yang berjumlah 20 orang siswa. Subjek penelitian ini adalah guru PKn kelas I dan siswa kelas I SD NEGERI 014673 Mekar Sari, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus, setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Hasil perbandingan observasi penelitian guru pada siklus I adalah sebesar 21% sedangkan pada siklus II sebesar 29%. Kata kunci: Metode Pembelajaran Jigsaw